2019
DOI: 10.1080/23279095.2019.1570929
|View full text |Cite
|
Sign up to set email alerts
|

Using the inventory of problems – 29 (IOP-29) with the Test of Memory Malingering (TOMM) in symptom validity assessment: A study with a Portuguese sample of experimental feigners

Abstract: This study tested whether combining the Inventory of Problems-29 (IOP-29) with the Test of Memory Malingering (TOMM) would increase sensitivity in the detection of experimentally feigned mental health problems, compared to using either test alone. Additionally, it also evaluated (a) the effects of administration order of these two tests and (b) the cultural and linguistic applicability of these tests to a European Portuguese population. The IOP-29 and TOMM were administered to a community sample of 100 nonclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 51 publications
4
26
1
Order By: Relevance
“…Indeed, the five SIMS subscales were not designed to detect the overreporting of mental health problems, but to determine which types of psychopathology respondents tend to overreport when the SIMS Total Score is above the cut-off value [39]. Different cut-off values have been used in the literature (i.e., ≥ 14 [25]; ≥ 17 [39]; ≥ 19 [32], and even ≥ 24 [41]). A recent meta-analytic study encompassing 4,180 protocols supported the claim that the specificity of the SIMS may be unsatisfactory when the traditional cut-offs (i.e., ≥ 15 and ≥ 17) are adopted [40].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the five SIMS subscales were not designed to detect the overreporting of mental health problems, but to determine which types of psychopathology respondents tend to overreport when the SIMS Total Score is above the cut-off value [39]. Different cut-off values have been used in the literature (i.e., ≥ 14 [25]; ≥ 17 [39]; ≥ 19 [32], and even ≥ 24 [41]). A recent meta-analytic study encompassing 4,180 protocols supported the claim that the specificity of the SIMS may be unsatisfactory when the traditional cut-offs (i.e., ≥ 15 and ≥ 17) are adopted [40].…”
Section: Methodsmentioning
confidence: 99%
“…A further example is the Inventory of Problems-29 (IOP-29) [22], a 29-item easy-to-use measure of non-credible mental and cognitive symptoms. Studies using this instrument yielded encouraging results in the detection of malingering [23,24] and indicated that it can be used in a multimethod symptom validity assessment along with TOMM [25]. Another example is the Structured Inventory of Malingered Symptomatology (SIMS) [26] is a 75-item multi-axial self-report questionnaire validated with clinical-forensic, psychiatric, and non-clinical populations.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to available alternatives, the IOP-29 seems to offer some advantages. First, it is notably shorter than other popular stand-alone instruments such as the (Giromini, Barbosa et al, 2019;Viglione et al, 2017), and that it has increased classification accuracy compared to the SIMS, especially with psychosisrelated conditions (Giromini, Viglione, Pignolo, & Zennaro, 2018). Also of note is that it shows incremental validity when used either with the TOMM or MMPI compared to using each instrument alone (Giromini, Lettieri et al, 2019;.…”
mentioning
confidence: 99%
“…Its research profile is accumulating, a hallmark for use in legal settings" (Young et al, 2020, p. 9). Although the IOP-29 was published only relatively recently in 2017 (Viglione et al, 2017), all 12 published studies since then support its validity and effectiveness (Gegner et al, 2021;Giromini et al, 2018Giromini et al, , 2020aIlgunaite et al, 2020;Roma et al, 2020;Viglione et al, 2017Viglione et al, , 2019Winters et al, 2020). Specifically, the results of these studies suggest that (a) the validity and classification accuracy of the IOP-29 compares favorably to that of popular measures like the Structured Inventory of Malingered Symptomatology (SIMS; Smith & Burger, 1997) (Giromini et al, 2018) or Rey Fifteen-Item Test (FIT; Lezak, 1995;Rey, 1941) (Gegner et al, 2021); (b) the IOP-29 is similarly valid when addressing feigning of different conditions such as depression, neuropsychological impairment, psychosis and/or PTSD (e.g., Giromini et al, 2020b;Ilgunaite et al, 2020;Winters et al, 2020); (c) the validity of the IOP-29 is maintained both when adopting a simulation/analogue (e.g., Gegner et al, 2021) and when relying on a known-groups comparison (Roma et al, 2020) research paradigm; (d) the IOP-29 yields incremental validity when used in combination with other SVTs (Giromini et al, 2019) or PVTs (Giromini et al, 2020a); (e) the IOP-29 preserves its effectiveness also when used outside the USA, in countries such as Australia (Gegner et al, 2021), the UK (Winters et al, 2020), Italy (Giromini et al, 2018), Portugal (Giromini et al, 2020a), or Lithuania (Ilgunaite et al, 2020).…”
Section: Distinctive Features Of the Iop-29mentioning
confidence: 99%
“…For the summary findings described in this section focused on mTBI, we thus included the latter group only, which was comprised of 19 experimental simulators and 18 mTBI patient controls. Giromini et al (2020a) administered the European Portuguese version of the IOP-29 along with the Test of Memory Malingering (TOMM; Tombaugh, 1996) to 100 adult Portuguese volunteers instructed to feign either depression (n = 50) or mTBI (n = 50). The current mini-review thus inspected the latter group only, comprised of 50 Portuguese feigners of mTBI.…”
Section: Viglione Et Al (2017)mentioning
confidence: 99%